Transfigurasi Yesus Sebagai Model Spiritualitas Orang Percaya - Pensensius Emen; Hendi Hendi (Jurnal Teologi Berita Hidup, 2021)
This article highlights an important event of the transfiguration of Jesus on the Mount of Tables which is recorded in the gospels from the writings of Origen and John of Damascus. The results of this paper show a reality that will be experienced by believers in spirituality until the second coming of the Lord, namely the form of divine light that is the same as God and the form of a body or flesh that will glow in glory when undergoing transfiguration. Purpose This article gives hope for every believer, in the struggle for spirituality will become like the radiant God. So the transfiguration event showed a state that transformed the conditions of mortality to divinity as experienced by the Lord Jesus Christ.Artikel ini menyoroti sebuah peristiwa penting transfigurasi Yesus digunung Tabor yang dicatat dalam Injil dari tulisan Origen dan Yohanes dari Damaskus. Hasil dari tulisan ini memperlihatkan suatu kenyataan yang akan orang percaya alami di dalam spiritualitas hingga pada saat kedatangan Tuhan yang kedua kali yaitu wujud terang ilahi yang sama seperti Allah dan wujud rupa tubuh atau daging yang akan bercahaya dalam kemuliaan ketika mengalami transfigurasi. Penulis melakukan riset literatur untuk menyatakan Tujuan Artikel ini  memberi pengharapan bagi setiap orang percaya, dalam pergumulan akan spiritualitas akan menjadi serupa dengan Allah yang bercahaya. Jadi peristiwa transfigurasi memperlihatkan suatu keadaan yang mentransformasi kondisi kefanaan kepada keilahian seperti yang dialami oleh Tuhan Yesus Kristus.